2006
DOI: 10.1212/01.wnl.0000233841.75824.0f
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Na + channelopathies

Abstract: Abstract-Background:Muscle channelopathies such as paramyotonia, hyperkalemic periodic paralysis, and potassiumaggravated myotonia are caused by gain-of-function Na ϩ channel mutations. Methods: Implementation of a threedimensional radial 23 Na magnetic resonance (MR) sequence with ultra-short echo times allowed the authors to quantify changes in the total muscular 23 Na signal intensity. By this technique and T2-weighted 1 H MRI, the authors studied whether the affected muscles take up Na ϩ and water during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 42 publications
3
49
0
3
Order By: Relevance
“…The effects of Ca 2+ observed in this study are also consistent with the observation that in normal muscle fibers, increased [Ca 2+ ] o hyperpolarizes the resting membrane potential (36) (16,45). Increased [Na + ] i is an important factor for activation of the Na + /K + pump (50,51), and Na + /K + pump stimulation improves membrane excitability and contractility in normal muscles with reduced Na + and/or K + gradients (52)(53)(54).…”
Section: Elevated [K + ] O Produced Sustained Weakness Of Isolated Musupporting
confidence: 90%
See 1 more Smart Citation
“…The effects of Ca 2+ observed in this study are also consistent with the observation that in normal muscle fibers, increased [Ca 2+ ] o hyperpolarizes the resting membrane potential (36) (16,45). Increased [Na + ] i is an important factor for activation of the Na + /K + pump (50,51), and Na + /K + pump stimulation improves membrane excitability and contractility in normal muscles with reduced Na + and/or K + gradients (52)(53)(54).…”
Section: Elevated [K + ] O Produced Sustained Weakness Of Isolated Musupporting
confidence: 90%
“…The original "normokalemic" periodic paralysis family described by Poskanzer and Kerr (43) and subsequently shown to harbor the Met1592Val mutation in the Na V 1.4 gene (42), showed a sensitivity to oral ingestion of K + even though the plasma [K + ] remained in the normal range during attacks. The phenotype associated with the Met1592Val mutation can be heterogeneous, though, with other reports indicating attacks of weakness associated with mild hyperkalemia or with cold sensitivity (44,45). We observed that raising [K + ] o from 4 to 8 mM produced only transient weakness in isolated mutant EDL muscle.…”
Section: Elevated [K + ] O Produced Sustained Weakness Of Isolated Mumentioning
confidence: 41%
“…However, in vitro and in vivo studies have shown that increased sodium influx and membrane depolarization of cooled PC fibers persist for hours. 24,25,30 This is in agreement with weakness lasting up to 8 h in PC patients, compared with that in hyperkalemic PP, which lasts from 30 min to 2 h. The larger sodium influx and the more pronounced sustained depolarization in PC (by 40 mV) than in hyperkalemic PP (by 30 mV) 24,25,30 may aggravate the T-tubular and myoplasmic disequilibrium and require more time for recovery.…”
Section: Hyperkalemic Pp: Is the Incomplete Slow Inactivation Importasupporting
confidence: 71%
“…3), corresponding to a gain-of-function defect. 10,21 As a result, sodium influx is increased, as shown in vitro 24 and in vivo 25 (FIGS. 4 and 5).…”
Section: 16mentioning
confidence: 78%
See 1 more Smart Citation